Global Market Position and Demand Elasticities of Indonesian Areca Nut: An AIDS Model Analysis - Futrinelsa, Silviony; Suharno, Suharno; Utami, Anisa Dwi (Universitas Panji Sakti, 2025)
This study aims to analyze the market position and competitiveness of Indonesian areca nut exports in the global market using the Almost Ideal Demand System (AIDS) model. Indonesia has remained the dominant exporter of areca nut globally, holding over 50% of the market share from 2012 to 2024. However, recent fluctuations in export value and competition from other major exporters such as Myanmar, Thailand, and India highlight the need for a deeper understanding of market dynamics. The analysis utilizes secondary data under HS Code 080280, spanning the 2012–2024 period, and employs the Seemingly Unrelated Regression (SUR) approach to estimate own-price, cross-price, and expenditure elasticities. Results indicate that Indonesia’s areca nut exports are price inelastic, suggesting limited responsiveness to price changes. Cross-price elasticity values reveal complementary relationships with India and Myanmar, as well as a substitutive relationship with Thailand. Expenditure elasticity further classifies Indonesian areca nut as a normal good, in contrast to Thailand and Myanmar’s luxury classification, and India’s categorization as an inferior good. These findings provide critical insights for developing strategies to enhance the competitiveness and export performance of Indonesian areca nut in international markets.